THE URGENCY OF USING TECHNOLOGY IN BROADCASTING ISLAMIC EDUCATIONAL MATERIALS TO FORM RELIGIOUS AWARENESS IN SOCIETY - Wahyuningsih, Fitri; Susanti , Riri; Hakki, Saddam; Azmi , Ulil (Antis Publisher, 2024)
Objective: This study aims to explore the challenges and effectiveness of using technology in broadcasting Islamic religious education materials to enhance religious awareness in society. Method: A library research approach was employed, utilizing scientific journal articles and research reports as primary sources to examine the role of technology in religious education. Results: The findings highlight that effective technologies for disseminating Islamic religious education include social media platforms (YouTube, Instagram, TikTok), learning applications, podcasts, webinars, and the digitization of Islamic books. These technologies enhance accessibility, foster interactive learning, and broaden the reach of religious materials. Furthermore, the use of technology has led to increased religious understanding and practice, strengthening community religious awareness. However, challenges remain, such as limited access in remote areas, low digital literacy, difficulties in filtering valid information, and an over-reliance on technology that may reduce direct teacher-community interaction. Novelty: This study contributes to the understanding of how technology can be harnessed to improve Islamic religious education, while also addressing the barriers and limitations faced in its implementation, offering insights into overcoming these challenges for more effective dissemination of religious knowledge.